(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
This study looks at how emotions affect language learning. Learner’s feelings play an important role in their motivation and ability to use a new language. Positive emotions like confidence and interest help students learn better, while negative emotions such as; fear and anxiety can make learning more difficult. Creating a positive and supportive learning environment is important for improving language skills.